Orofacial manifestations of hematological disorders: Anemia and hemostatic disorders - Titilope A Adeyemo; Wasiu L Adeyemo; Adewumi Adediran; Abd Jaleel A Akinbami; Alani S Akanmu (Wolters Kluwer Medknow Publications, 2011)
The aim of this paper is to review the literature and identify orofacial manifestations of hematological diseases, with particular reference to anemias and disorders of hemostasis. A computerized literature search using MEDLINE was conducted for published articles on orofacial manifestations of hematological diseases, with emphasis on anemia. Mesh phrases used in the search were: oral diseases AND anaemia; orofacial diseases AND anaemia; orofacial lesions AND anaemia; orofacial manifestations AND disorders of haemostasis. The Boolean operator "AND" was used to combine and narrow the searches. Anemic disorders associated with orofacial signs and symptoms include iron deficiency anemia, Plummer-Vinson syndrome, megaloblastic anemia, sickle cell anemia, thalassaemia and aplastic anemia. The manifestations include conjunctiva and facial pallor, atrophic glossitis, angular stomatitis, dysphagia, magenta tongue, midfacial overgrowth, osteoclerosis, osteomyelitis and paraesthesia/anesthesia of the mental nerve. Orofacial petechiae, conjunctivae hemorrhage, nose-bleeding, spontaneous and post-traumatic gingival hemorrhage and prolonged post-extraction bleeding are common orofacial manifestations of inherited hemostatic disorders such as von Willebrand's disease and hemophilia. A wide array of anemic and hemostatic disorders encountered in internal medicine has manifestations in the oral cavity and the facial region. Most of these manifestations are non-specific, but should alert the hematologist and the dental surgeon to the possibilities of a concurrent disease of hemopoiesis or hemostasis or a latent one that may subsequently manifest itself.